SOME OBSERVATIONS ON THE FISHERY AND BIOLOGY OF SARDINELLA FIMBRIATA (VAL.) AT VIZHINGAM - Bennet, P Sam (Indian Journal of Fisheries, 2011)
The sardines, Sardinella spp., constitute an important resource along the coastsof India. Commercial fishing in the inshore waters has shown that the differentspecies of sardine are concentrated at different localities all along the coast. Thusthe oil sardine Sardinella longiceps is localised along the Kerala and Mysore coasts.S. fimbriata occur in commercial quantities along the South Kerala and North Mysorecoasts. S. albella is not abundant anywhere on the west coast, but at timesoccurs in small quantities along the coast. On the south-west coast S. clupeoides,along with 5. sirm and S. melanura forms a minor fishery during December (Bennet,1965). All the six species have been caught in the inshore waters up to 10 km fromthe land. On the east coast of India S. fimbriata, S. albella, S. gibbosa and S. sirmoccur in commercial quantities along the Madras and Andhra coasts. Other sardinesoccur only in small quantities.